Polymorphisms in mitochondrial ribosomal protein S5 (MRPS5) are associated with leprosy risk in Chinese. - Yan Xing; Jun He; Yan Wen; Jian Liu; Yuangang You; Xiaoman Weng; Lianchao Yuan; Li Xiong; Xiaohua Chen; Ying Zhang; Huan-Ying Li (Public Library of Science (PLoS), 2020)
Leprosy is an infectious disease caused by Mycobacterium leprae (M. leprae), with about 210,000 new cases per year worldwide. Although numerous risk loci have been uncovered by genome-wide association studies, the effects of common genetic variants are relatively modest. To identify possible new genetic locus involved in susceptibility to leprosy, whole exome sequencing was performed for 28 subjects including 14 patients and 12 unaffected members from 8 leprosy-affected families as well as another case and an unrelated control, and then the follow-up SNP genotyping of the candidate variants was studied in case-control sample sets. A rare missense variant in mitochondrial ribosomal protein S5 (MRPS5), rs200730619 (c. 95108402T>C [p. Tyr137Cys]) was identified and validated in 369 cases and 270 controls of Chinese descent (Padjusted = 0.006, odds ratio [OR] = 2.74) as a contributing factor to leprosy risk. Moreover, the mRNA level of MRPS5 was downregulated in M. leprae sonicate-stimulated peripheral blood mononuclear cells. Our results indicated that MRPS5 may be involved in leprosy pathogenesis. Further studies are needed to determine if defective MRPS5 could lead to impairment of energy metabolism of host immune cells, which could further cause defect in clearing M. leprae and increase susceptibility to infection.